1995
DOI: 10.1111/j.1365-2958.1995.mmi_18020301.x
|View full text |Cite
|
Sign up to set email alerts
|

sbmC, a stationary‐phase induced SOS Escherichia coli gene, whose product protects cells from the DNA replication inhibitor microcin B17

Abstract: Microcin B17 (MccB17) is a ribosomally synthesized peptide antibiotic of 43 amino acids that induces double-strand breaking of DNA in a DNA gyrase-dependent reaction. As a consequence, the SOS regulon is induced and massive DNA degradation occurs. In this work we have characterized an Escherichia coli gene, sbmC, that in high copy number determines high cell resistance to MccB17. sbmC encodes a cytoplasmic polypeptide of 157 amino acids (M(r), 18,095) that has been visualized in SDS-polyacrylamide gels. The ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
53
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 31 publications
3
53
0
Order By: Relevance
“…Thus, amplification of gyrI and mdfA may prevent MMC from interacting with DNA, its macromolecular target. Amplification of gyrI has previously been shown to protect cells from the action of microcin B17, a DNA-cleaving agent (6). This compound causes double-stranded DNA breaks in vivo and in vitro only in concert with DNA gyrase (39).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, amplification of gyrI and mdfA may prevent MMC from interacting with DNA, its macromolecular target. Amplification of gyrI has previously been shown to protect cells from the action of microcin B17, a DNA-cleaving agent (6). This compound causes double-stranded DNA breaks in vivo and in vitro only in concert with DNA gyrase (39).…”
Section: Discussionmentioning
confidence: 99%
“…9 In E.coli, the expression of sbmC is induced by DNA-damaging agents, possesses a quasicanonical LexA box and much like umuDC, the expression of sbmC is RecA and LexA dependent. 9 Thus, upregulation of umuD, lexA, dinP and sbmC by all nine FQs is likely LexA dependent. Figure 1b shows some of the more responsive clones as well as those related to the SOS response.…”
Section: Fq-responsive Promoters Involved In Stress Responsementioning
confidence: 99%
“…8 ) The sbmC gene was originally Salmonella responses to fluoroquinolones G Yim et al identified by its ability to confer resistance to MccB17 at high copy number. 9 MccB17 is a peptide antibiotic that induces double-stranded breaks in DNA in a DNA gyrase-dependent manner. 9 In E.coli, the expression of sbmC is induced by DNA-damaging agents, possesses a quasicanonical LexA box and much like umuDC, the expression of sbmC is RecA and LexA dependent.…”
Section: Fq-responsive Promoters Involved In Stress Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Independently, Baquero et al (26) reported that the gyrI gene (identical to the sbmC gene) belongs to the SOS regulon. The inactivation of GyrI causes cells to be more sensitive to microcin B17, whereas its overexpression yields microcin B17-resistant cells (26).…”
mentioning
confidence: 99%